Polling Consumers: The Rise of Market Research Surveys in Canada, 1929-1941 - Robinson, Daniel (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1997)
AbstractConsumer sample surveys, the predecessor of opinion polling, emerged in the late 1920s as a response to the marketing problems of lacklustre demand and inefficient distribution. In conjunction with Dominion Bureau of Statistics marketing data, consumer surveys were conceived and championed as the demandside corollary of rationalised manufacturing methods. By providing quantitative measures of buyer wants and behaviours, they could improve the efficiency and effectiveness of advertising, thus boosting aggregate consumer spending. Chief among the early promoters and practitioners of consumer surveys were advertising agencies, market research firms, and newspaper and magazine publishers. While some US historians of mass marketing have characterised the phenomenon as a democratic leveller of consumption, Canadian consumers, as represented in market surveys, were not a facsimile of the general population. They were disproportionately married and female, urban and English-speaking, and, most of all, drawn from middle-to-upper-income ranks.